The Role of Guest Experience in Providing Excellent Service to Guests at Sofitel Bali Nusa Dua - Arsani, Putu Satya Dewi; Wulan, Anak Agung Istri Ratna Sari; Pitanatri, Made Uttari (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study analyzes the role of guest experience in excellent service at Sofitel Bali Nusa Dua using qualitative descriptive methods. Data were collected through interviews, observations, and documentation. The results showed that 77% of services were in accordance with expectations, while 23% were not. This discrepancy was caused by the imbalance of responsibility between the butler and guest experience sections when escorting and farewelling VIP guests, as well as the lack of awareness of grooming in certain shifts. The suggestions given are the need for clarity of duties between the two sections and grooming checks by the Leader in the afternoon shift